Jio Platforms Ltd. announces joint venture with SES - Reliance Industries Limited (2022)
Jio Platforms Ltd and leading global satellite-based content connectivity solutions provider SES have announced a JV, Jio Space Technology Limited, to deliver the next generation scalable and affordable broadband services in India leveraging satellite technology.